2007
DOI: 10.1016/j.brainres.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 (PGE2) inhibits glutamatergic synaptic transmission in dorsolateral periaqueductal gray (dl-PAG)

Abstract: The purpose of this study was to determine the role of prostaglandin E 2 (PGE 2 ) in modulating neuronal activity of the dorsolateral periaqueductal gray (dl-PAG) through excitatory and inhibitory synaptic inputs. First, whole cell voltage-clamp recording was performed to obtain excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) of the dl-PAG neurons. Our results show that PGE 2 significantly decreased the frequency of miniature EPSCs and amplitude of evoked EPSCs. The effects were mimicked by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…We have confirmed that all the cells included for data analysis in this report located in the dl-PAG (Lu et al, 2007;Xing and Li, 2007). Whole cell patch-clamp experiments were performed and experimental data were collected from 68 dl-PAG neurons.…”
Section: Location Of the Recording Pipettesupporting
confidence: 63%
See 1 more Smart Citation
“…We have confirmed that all the cells included for data analysis in this report located in the dl-PAG (Lu et al, 2007;Xing and Li, 2007). Whole cell patch-clamp experiments were performed and experimental data were collected from 68 dl-PAG neurons.…”
Section: Location Of the Recording Pipettesupporting
confidence: 63%
“…All drugs were dissolved in the aCSF solution immediately before they were used. According to experimental protocol, the drugs were delivered into the recording chamber at final concentrations using syringe pumps during the experiment (Lu et al, 2007;Xing and Li, 2007). The responses of EPSCs and IPSCs of the dl-PAG to application of drugs were recorded after control data were collected.…”
Section: Drugs and Their Application-ttxmentioning
confidence: 99%
“…Likewise, if a compound augments transmitter release an attenuation of the second pulse to paired stimuli is seen. Thus, facilitation and attenuation of the PPR are generally used to reflect effects of a certain compound on the presynaptic process [17,18,23]. …”
mentioning
confidence: 99%
“…It has been reported that the activation of EP 3 receptors by using sulprostone, an EP 3 receptor agonist, inhibits the synaptic glutamate release in the dorsolateral PAG [22]. As a descending pathway, the dorsolateral PAG plays an inhibitory role in regulating nociception via the medulla [9].…”
Section: Discussionmentioning
confidence: 99%